High-resolution synchrotron x-ray diffraction study of Zr-rich compositions of Pb ZrxTi1-x)O3(0.525≤x≤0.60): Evidence for the absence of the rhombohedral phase - Singh A.K.; Pandey D.; Yoon S.; Baik S.; Shin N. (My University, 2025)
Results of Rietveld analysis of the synchrotron x-ray diffraction data on Pb (Zrx Ti1-x) O3 (PZT) for 0.525≤x≤0.60 are presented to show the absence of rhombohedral phase on the Zr-rich side of the morphotropic phase boundary. Our results reveal that the structure of PZT is monoclinic in the Cm space group for 0.525≤x≤0.60. The nature of the monoclinic distortion changes from pseudotetragonal for 0.525≤x≤0.54 to pseudo-rhombohedral for x<0.54. © 2007 American Institute of Physics.